PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR - Panjaitan, Yunia; Wijaya, Bandi (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2014)
Working capital is needed for day to day operations of a fi rm. The primary purpose of this research was to examine the effect of working capital management including average receivable period, average inventory period, average payment period, and cash conversion cycle on operating income ratio of firms. Debt ratio, size, financial assets to total asset ratio, and sales growth have been used as control variables. In this research, samples have used 119 manufacture firms listed on Indonesia Stock Exchange for period 2008-2012. The analytical method used is the analysis descriptive and analysis of panel data regression with random effect model. The results show that there is a negative significant effect between average receivable period, average inventory period, and cash conversion cycle on operating income ratio. It means, managers can increase the profitability of the firm by shortening the cash conversion cycle, average receivable period, and average inventory period to a possible minimum level.